Decree of the Board of Directors of The General Authority for Investment And Free Zones No. 119 of the year 2019 Promulgating the Regulations of Investment Zones Regime = وزارة الاستثمار والتعاون الدولي قرار محجلس إدارة الهيئة العامة للاستثمار والمناطق الحرة رقم 119 لسنة 2019 بإصدار لائحة نظام المناطق الاستثمارية - Egypt; The middle east library for economic services, translator. (2025)
Decree of the board of directors of the general authority for investment and free zones no. 119 of the year 2019 promulgating the regulations of investment zones regime – chapter 1: general provisions – chapter 2: procedures of establishing a free zones -- chapter 3: board of directors in investment zones -- chapter 4: executive offices in investment zones -- chapter 5: completion of projects established in the investment zone قرار مجلس إدارة الهيئة العامة للاستثمار والمناطق الحرة رقم 119 لسنة 2019 بإصدار لائحة نظام المناطق الاستثمارية – الفصل الأول أحكام عامة – الفصل الثانى إجراءات إقامة منطقة استثمارية – الفصل الثالث مجالس إدارة المناطق الاستثمارية – الفصل الرابع المكاتب التنفيذية بالمناطق الاستثمارية – الفصل الخامس انتهاء المشروعات القائمة بالمنطقة الاستثمارية